2014
DOI: 10.1371/journal.pone.0110821
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Conjunctivochalasis on Visual Quality of Life: A Community Population Survey

Abstract: Conjunctivochalasis (Cch) is a very common ocular disorder, which can cause an unstable tear film and ocular discomfort. The study of vision-related quality of life (VR-QoL) in a community population with Cch can provide a better understanding of the impact of Cch on common people than objective clinical examinations alone. This cross-sectional comparative study enrolled 360 participants ≥40 years old living in Sanle Community, Shanghai. In the study, 198 subjects were diagnosed with Cch and 86 with dry eye sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
1
17
1
Order By: Relevance
“…The eyelid laxity, more common in older individuals, has been reported to be associated with dry eye symptoms and abnormal tear parameters. It has impacts on tear function that lead to a greater exposure and increased irritation [49,50], which could explain our findings regarding the increased ocular redness with age.…”
Section: Discussionmentioning
confidence: 75%
“…The eyelid laxity, more common in older individuals, has been reported to be associated with dry eye symptoms and abnormal tear parameters. It has impacts on tear function that lead to a greater exposure and increased irritation [49,50], which could explain our findings regarding the increased ocular redness with age.…”
Section: Discussionmentioning
confidence: 75%
“…Similar to dry eye, Cch has been found to be more frequent in older individuals 6,7 and adversely affects vision-related quality of life. 8 In fact, one study in a German population demonstrated that the presence of any Cch was associated with dry eye symptoms. 9 Two other studies in Chinese and German populations examined Cch location and found that nasal conjunctivochalasis (NCch) was associated with higher dry eye symptoms compare with nonnasal conjunctivochalasis (non-NCch) and no conjunctivochalasis (no-Cch).…”
mentioning
confidence: 99%
“…9 Two other studies in Chinese and German populations examined Cch location and found that nasal conjunctivochalasis (NCch) was associated with higher dry eye symptoms compare with nonnasal conjunctivochalasis (non-NCch) and no conjunctivochalasis (no-Cch). 8,10 With respect to signs, several studies in Chinese, Japanese, and German populations have demonstrated an association between NCch and bulbar conjunctival hyperemia, 10 decreased tear film stability, 8 and higher rose Bengal staining scores. 5 Despite the abundance of data internationally, the epidemiology of Cch has not been as well studied in the United States.…”
mentioning
confidence: 99%
“…Anatomic changes, such as conjunctivochalasis and eyelid laxity are associated with DE symptoms and abnormal tear parameters [40-41]. As with other involution changes, both of these entities are more common in older individuals [40, 42-43].…”
Section: Dry Eye and Agingmentioning
confidence: 99%